Appeals in Modern Rhetoric : An Ordinary Language Approach - Killingsworth, M. Jimmie (Book collections on Project MUSE., 2005)
Appeals in Modern Rhetoric: An Ordinary-Language Approach introduces students to current issues in rhetorical theory through an extended treatment of the rhetorical appeal, a frequently used but rarely discussed concept at the core of rhetorical analysis and criticism. Shunning the standard Aristotelian approach that treats ethos, pathos, and logos as modes of appeal, M. Jimmie Killingsworth uses common, accessible language to explain the concept of the rhetorical appeal- meaning the use of language to plead and to please. The result is a practical and innovative guide to understanding how per.